H.P. van Tuyll van Serooskerken, Small Countries in a Big World: The Belgian-Dutch Conflict at Versailles, 1919 - Samuël Kruizinga (BMGN: Low Countries Historical Review, 2017)
H.P. van Tuyll van Serooskerken, Small Countries in a Big World: The Belgian-Dutch Conflict at Versailles, 1919 (Leiden: Brill, 2017, 268 pp., isbn 978 9 004 31469 6).